Psychological and sociological perspectives for good governance of sustainable nanotechnology development in Malaysia - Nur Aizat, K.; Lee, Khai Ern *; Siow, Kim Shyong; Mazlin, Mokhtar * (Springer, 2019)
Nanotechnology is developed to improve public well-being, stimulate economic growth, and provide environmental solutions, which are essential for sustainable development. However, the uncertain risks of nanotechnology may destroy public confidence and impede nanotechnology development from facilitating sustainable development. Thus, public perception is a critical component to understand public acceptance of nanotechnology and for nanotechnology development to be well governed. Good governance of nanotechnology is vital to ensure the benefits are distributed equitably while protecting the public from the risks. Hence, this study was based on psychological and sociological approaches with intervention from moderators, that is, media coverage, technology and economic development, benefit and risk of nanoapplications, and benefit and risk information. A survey was conducted in Malaysia to determine the effects of moderators’ influence on public perceptions. The study found, based on a psychological and sociological approach, that the moderating effects of moderators influenced public perception in a manner that increased or decreased the benefit and risk perception of nanotechnology. The results later serve as an input for recommending good governance strategies for applying nanotechnology to sustainable development.